Influence of N-limitation on malic enzyme isoforms and lipogenesis of Cunninghamella bainieri 2A1 - Hamid A.A.; Shuib S.; Taha E.M.; Omar O.; Khalil M.S.; Kader A.J.A.; Mohd Hafez Mohd Isa (2024)
Indexed by WOS/SCOPUS